(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2024)
Primary and secondary infertility are two main categories into which infertility can be divided. Primary infertility is the inability to procreate in a couple that has never had a child, while secondary infertility is the inability to conceive after a previous live birth. Infertility may be caused by specific pathology in males (20-30%), females (30-50%), and the inexplicable (25-30%). Uterine fibroid (UF) is observed in 5-30% of female infertile patients. A case report of a 32-year-old married female who has been experiencing secondary infertility with UF for four years is presented below. After a two-year period of normal conjugal life, the couple had consulted with a gynecologist, who diagnosed her with UF (>3cm). However, they were unable to conceive spontaneously. Despite two years of conventional medical treatment, she did not achieve a successful outcome. Consequently, surgery was recommended. She was treated with constitutional homoeopathic medications (Sepia and Natrum muriaticum) for a period of six months at this juncture. She conceived spontaneously and delivered a healthy female child at full term without any complications. This case illustrates the beneficial impact of constitutional homoeopathic treatment on secondary subfertility associated with UF.